PvdA uislagavond 29-11-1972 Koopmansbeurs Amsterdam. V.l.n.r. Van Mierlo, Den Uyl. Op de tv: Witteveen, Van Meekeren - Koers, Ab. (1972)
PvdA uislagavond 29-11-1972 Koopmansbeurs Amsterdam. V.l.n.r. Van Mierlo, Den Uyl. Op de tv: Witteveen, Van Meekeren.